The Effect of Drying Air Temperature and Humidity on the Drying Kinetics of Kenaf Core - Suhaimi, Misha (trans tech publications inc., 2013)
Drying kinetics of kenaf core was investigated in a Low Temperature and Humidity Chamber Test. The drying experiments were carried out at temperature of 45, 50 and 550C and air relative humidity of 10, 20 and 30% using a constant air velocity of 1.0 m/s. The moisture content data at various drying air conditions were converted to moisture ratio and plotted against time to obtain the drying curves for each experimental data. The curves were fitted to eight different thin layer drying models to determine a suitable model for drying of kenaf core. The fit quality of the models was evaluated based on their coefficient of determination (R2), reduced chi-square (χ2) and root mean square error (RMSE). Among the eight models, Two Term model is the best model for describing the drying behavior of kenaf core. The drying air temperature gave more significant effect on the drying kinetic of kenaf core compared to the drying air relative humidity under the experimental conditions studied.